Managing the IE (Industrial Engineering) mindset: A quantitative investigation of Toyota's practical thinking shared among employees - Phillip Marksberry; David C. Parsley (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The goal of this work was to investigate the managerial practices of today to understand if Toyota is sheltering themselves from these newer practices or embracing them like most believe. Design/methodology/approach: This work utilizes a new form of data mining named Latent Semantic Analysis (LSA) to analyze an organizations ideal management practices. Findings: This work shows quantitatively that TPS favors earlier versions of industrial engineering compared to the optimization techniques available today. Originality/value: The use of data mining to analyze organizational management practices.
Keywords: 650; Toyota Production System (TPS); industrial engineering; lean manufacturing; dimensional reduction algorithm; management; scientific management